The Construction of (k,3)-Arcs in PG(2,9) by Using Geometrical Method - Mahmod, Adil; Al-Mukhtar, Amal .SH.; Kareem, Fatema.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, we construct projectively distinct (k,3)-arcs in the projective plane PG(2,9) by applying a geometrical method. The cubic curves have been been constructed by using the general equation of the cubic. We found that there are complete (13,3)-arcs, complete (15,3)-arcs and we found that the only (16,3)-arcs lead to maximum completeness